EXPERIMENTAL EVALUATION OF SYNTHETIC INDUCTORS APPLIED IN PASSIVE SHUNT CIRCUITS TO VIBRATION MITIGATION - Zambolini-Vicente, Bruno Gabriel Gustavo Leonardo; Lima, Antônio Marcos Gonçalves de; Finzi Neto, Roberto Mendes (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In the passive vibration attenuation, the electronic circuits containing synthetic impedances to resonate with a typical mechanical vibration problem is the simplest way to avoid the large volume and weight of traditional inductors, which need to be large due to low-frequency scenario of mechanics dynamics. In order to construct those simulated inductors to provide energy transfer from mechanical vibration to electrical circuit, schemes with operational amplifiers are used, that deliver high values of henrys with formation law depending of resistors and capacitors connected to these amplifiers. In this study it was held the experimental evaluation of circuits employing three kinds of synthetics inductors, configurable between serial and parallel arrangements, applying three types of shunts circuits described in the literature, tuned to mitigate three modes of a structure. The results were organized to provide an overview of the attenuation capability, showing the impact of circuit tunings for each vibrate mode. Thus, the experiments indicate, for example, that for the rated circuits, the tuning with the greatest attenuation is Wu Parallel when setup to the first mode. Overall, the results point to a potential attenuation capability, that can be further enhanced from the use of other circuits more adapted in the literature.